دور معايير المحاسبة الدولية في تفعيل حوكمة الشركات - غربي, امال شهرزاد (My University, 2021)
This study attempts to highlight the role international accounting in activating corporate governance, and the degree of reliance on them in completely reducing the problems facing institutions, especially financial problems, the most important of which is the loss of confidence and credibility in the preparation of financial statements, as the international accounting standards committee works to issue accounting standards that comply and corporate governance is among these standards IAS/IFRS, where many countries and bodies have decided to adopt their accounting standards in order to bring about compatibility at the international level, and this is due to the importance and role that it contributed in the field of corporate governance support. This study concluded that there is a close relationship between international accounting standards and corporate governance, as international accounting standards play a major role in the development of the accounting profession, and this in turn is reflected in the establishment of corporate governance principles, especially those related to the preparation and presentation of financial accounting system
Keywords: international accounting standards, financial accounting system. corporate governance